The Clinical Pattern and Prevalence of Streptococcus mutans and Streptococcus sobrinus among Adult and Children Patients with Dental Caries - Nanik Zubaidah; Nur Dianawati; Rini Devijanti Ridwan; Toshiro Shirakawa; Kuntaman Kuntaman; Ernie Maduratna Setiawatie; Muhammad Iqbal Tanzil; Sri Kunarti (Association of Support to Oral Health Research (APESB), 2022)
Objective: To explore the clinical pattern, host factors, and presentation of Streptococcus mutans related to caries incidence among children and adults visiting Universitas Airlangga dental clinic. Material and Methods: This was an observational study with a cross-sectional approach with 50 patients in each group of carious children (6-12 years) and adults (18-35 years). Dental decay samples were taken by sterile excavator, put in a BHI's transport medium, and directly incubated overnight at 37 ºC. The next day, they were sub-cultured microbiologically in Tryptone Yeast Cystine Sucrose Bacitracin (TYCSB) selective medium. Bacterial species and serogroups were examined by PCR. All patient's data were collected from medical records and direct observation. Results: Caries were mostly media type in both children and adults. Oral hygiene (OHIS) in children was higher than in adults but not significantly different according to their DMFT. The highest scores for decay, missed and filled teeth were 16, 8 and 7, with an average of 6.82, 1.22 and 0.63, considered quite high. Conclusion: The prevalence of S. mutans was higher in children's caries than in adults, but among the adult patients the co-incidence of S. mutans and S. sobrinus was associated with higher DMFT. The mutans serotypes e, f, and d were more prevalent among children than adults.